Analisis Efektivitas Promosi Media Sosial dengan Menggunakan Metode Epic Model dan Pengaruhnya terhadap Keputusan Pembelian Produk di Kota Medan - Kurnia, Efry; Daulay, Raihanah; Aisha , Novi (Balance : Jurnal Akuntansi dan Manajemen, 2022)
Social media until now has had a big influence on the shape of a business. Through online promotion strategies published in influential information media in an area, it provides its own value and great attention from enthusiasts in each of these media, one of which is the Instagram social media on the media talk account which is very much appreciated, and the people of Medan city in looking for information and news that is up to date. Providing creative information with diverse and interesting promotions will have an influence on companies that load into the terrain so as to attract the public in purchasing decision activities from promotions loaded in medantalk. The analytical methods used in this study are the EPIC model method and multiple regression analysis. The results of the analysis using the EPIC model method are known that medantalk promotion has been effective in introducing to consumers interested in medantalk. The four variables used